NagRBt Is a Pleiotropic and Dual Transcriptional Regulator in Bacillus thuringiensis - Cao, Zhang-lei; Tan, Tong-tong; Zhang, Yan-li; Han, Lu; Hou, Xiao-yue; Ma, Hui-yong; Cai, Jun (Frontiers in Microbiology, 2018)
NagR, belonging to GntR/HutC family, is a negative regulator that directly represses the nagP and nagAB genes, which are involved in GlcNAc transport and utilization in Bacillus subtilis. Our previous work confirmed that the chitinase B gene (chiB) of Bacillus thuringiensis strain Bti75 is also negatively controlled by YvoABt, the ortholog of NagR from B. subtilis. In this work, we investigated its regulatory network in Bti75 and indicated that YvoABt was an N-acetylglucosamine utilization regulator primarily involved in GlcNAc catabolism, therefore YvoABt was renamed to NagRBt. The RNA-seq data revealed that 27 genes were upregulated and 14 genes were downregulated in the ΔnagR mutant compared with the wild-type strain. The regulon (exponential phase) was characterized by RNA-seq, bioinformatics software, electrophoretic mobility shift assays, and quantitative real-time reverse transcription PCR. In the Bti75 genome, 19 genes that were directly regulated and 30 genes that were indirectly regulated by NagRBt were identified. We compiled in silico, in vitro and in vivo evidence that NagRBt behaves as a repressor and activator to directly or indirectly influence major biological processes involved in amino sugar metabolism, nucleotide metabolism, fatty acid metabolism, phosphotransferase system, and the Embden–Meyerhof–Parnas pathway.